1997
DOI: 10.1007/bf02887998
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-9 mRNA in osteoporotic bone tissues

Abstract: Matrix metalloproteinases (MMPs), a sort of important enzymes involved in extracellular matrix metabolism, play critical roles in the process of tissues remodeling, wound healing and metastasis of tumors. Dot blot and in situ hybridization were used in this study to detect the expression and localization of MMP-9, an important proteolytic enzyme implicated in bone resorption in bone tissues. The results showed that the level of MMP-9 mRNA expression in osteoporotic bone tissues was significantly higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…A high expression of MMP-9 in osteoclasts has previously been detected (7). The present study demonstrated that, the levels of MMP-9 mRNA and protein expression in the OVX group were significantly higher in comparison with those in the sham group, which is consistent with the conclusions of a previous study (20). Similar trends were observed for MMP-9 expression as those detected for MMP-2 expression in the OVX group between 12 and 24 weeks after surgery.…”
Section: Discussionsupporting
confidence: 93%
“…A high expression of MMP-9 in osteoclasts has previously been detected (7). The present study demonstrated that, the levels of MMP-9 mRNA and protein expression in the OVX group were significantly higher in comparison with those in the sham group, which is consistent with the conclusions of a previous study (20). Similar trends were observed for MMP-9 expression as those detected for MMP-2 expression in the OVX group between 12 and 24 weeks after surgery.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, no difference in the frequency of TNFα expression was observed in the bone tissue of OP versus healthy women [ 37 ]. Upregulation of MMP-9 gene and protein expression in the PBMCs of the examined OP women is supported by the in situ hybridization results of others, which showed an increase in MMP-9 mRNA in osteoporotic bone tissue versus the normal controls [ 3 ]. However, some studies also reported decreased MMP-9 expression in the bone of the postmenopausal OP patients [ 38 ].…”
Section: Discussionsupporting
confidence: 62%
“…Excessive bone degradation in OP is thought to result from an increased activity of resorptive osteoclasts, which express proteases such as metalloproteinase (MMP-9) and cathepsin K. Cathepsin K, a papain-like cysteine protease, is considered a key player in the process of bone resorption [ 3 , 4 ]. Osteoclast differentiation and function are regulated by the tumor necrosis factor α (TNF α ), receptor activator of nuclear factor kappa B ligand (RANKL), and macrophage colony-stimulating factor (M-CSF).…”
Section: Introductionmentioning
confidence: 99%
“…Two major proteolytic enzyme classes, cathepsin k (a cysteine protease) and MMP 9 (a matrix metalloproteinase), are highly expressed during bone resorption leading to bone matrix degradation and are most abundant in osteoclasts (Logar et al 2007). Further, MMP 9 mRNA expression was reported to be higher in osteoporotic bone tissues compared with that of normal control group and is expressed by mono-and multinuclear osteoclasts and bone matrix lining cells (Haibo et al 1997). No significant difference was seen in MMP 14.…”
Section: Discussionmentioning
confidence: 92%